Histological and Histochemical changes in diabetic male rat liver and intestine: and protective effect of cinnamon oil. - AL – Shaikh, Mahera N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background:The diabetogenic agent alloxan is a selective necrosis of insulin producing cells .Alloxan accumulated rapidly in liver and pancreatic islets , this study was carried out to evaluate the antidiabetic effect of cinnamon oil on the destructive effect of alloxan in liver and intestine diabetic tissues . Materials and methods:Thirty male rats were used and divided into threegroups: Group I =10 animal controls, Group II =10 treated with alloxan, Group III = 10 treated with alloxan + cinnamon oil . Results:Liver and intestine tissues of diabetic groups revealed necrotic, degeneration of cells (histologically ) , increase in blood serum enzymes for acid and alkaline phosphatase , total protein ,cholesterol and triglycerides ( biochemically) , and increase in the activity of acid and alkaline phosphatase in liver and intestine tissues ( histochemically ). While diabetic group treated with cinnamon oil revealed decrease in all these parameters. Conclusions: Oral administration of cinnamon oil produce significant hypoglycemic effect restores liver function and normalize the histological, histochemical and biochemical abnormalities caused by diabetes in alloxan induced diabetic rats, this may be due to antioxidant effect of this herb.